A Literature Study on Complementary Therapies for the Management of Anemia in Adolescent Girls - Tri Sartika; Ayu Devita Citra Dewi (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Anemia is a common health issue among adolescent girls, primarily due to increased iron demands during growth and menstruation. This literature study aims to synthesize existing research on complementary therapies for managing anemia in this population. The study employed a literature review design with a systematic search of scientific articles published between 2018 and 2025. Data were collected from multiple electronic databases, including PubMed and Google Scholar, using keywords such as "anemia," "adolescent girls," "complementary therapy," "iron deficiency," "herbal medicine," and "nutritional intervention." Only peer-reviewed articles, clinical trials, systematic reviews, and meta-analyses published in English were included. The review found that natural interventions like Moringa oleifera leaf extract, beetroot juice, dates with lime juice, and educational programs are effective, affordable, and culturally acceptable for improving hemoglobin levels and anemia prevention. However, many studies have limitations such as small sample sizes and short intervention durations. Future research should focus on more rigorous designs with larger samples and longer follow-ups. Combining nutritional supplementation with health education offers a promising holistic approach to managing anemia in adolescent girls.